PELAYANAN KESEHATAN PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL DI PUSKESMAS GELA KECAMATAN TALIABU UTARA KABUPATEN PULAU TALIABU PROVINSI MALUKU UTARA - SAHUPALA, SAHIL; RORONG, ARIE JUNUS; PLANGITEN, NOVVA (Sam Ratulangi University, 2017)
Abstract: the purpose of this research is to find out how the development of healthcare participants in the BPJSClinics North District Kecamatan Gela Taliabu island of Taliabu North Maluku province. This study usesqualitative methods. Informant this research as many as 10 people including 5 as employees of clinics and 5 asa society (BPJS participants).Data collection techniques used are interviews, while data analysis is done with a qualitative interactive methodof analysis techniques from Miles and Hubermann.Based on the results of the research infrastructure is very minimal and limited medical tools, such as lack ofambulance which sometimes cannot be used because of the damage, the bed less, pusling vehicles (itinerantclinics) that are not function to load the service activity does not run optimally. Clinics Gela that have only 1person of the doctor and it's not the doctor, the nurse who is still less responsible in serving patients, as well asdrugs that have not been sufficient. Still kakunya the existing system in organizing special participant for thefirst administration BPJS, people still often mess around with the actual administration of the activities can beperformed once the patient handled/get advance treatment to get a reference letter. Clinics of Gela who wasalready quite well in providing services/redirection in the management of the BPJS files.Keywords: Service, Health, Participants Of The BPJS.